1999
DOI: 10.1021/ac981139j
|View full text |Cite
|
Sign up to set email alerts
|

Automated and Integrated System for High-Throughput DNA Genotyping Directly from Blood

Abstract: An automated and integrated system for DNA typing directly from blood samples has been developed. The multiplexed eight-array system is based on capillary microfluidics and capillary array electrophoresis. Three short-tandem-repeat loci, vWA, THO1, and TPOX, are coamplified simultaneously in a fused-silica capillary by a hot-air thermocycler. Blood is directly used as the sample for polymerase chain reaction (PCR) without any pretreatment. Modifications of standard protocols are necessary for direct PCR from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 21 publications
0
50
0
Order By: Relevance
“…Considering that M13/pUC is a well established cloning vector and the assay was carried out in a buffer environment, the prospective inhibition from a matrix of 'real' sample (blood sample and/or with whole target cells) was not present. The PC plastic serpentine channel PCR micro reactor discussed in this study held a maximum volume of 40 ml and demonstrated a high sensitivity of amplifying 10 E. coli cells (50 fg DNA) from 2% blood sample, as compared to on-chip (glass-silicon) amplification of ng amounts of WBC DNA obtained by filtration from a sample containing 3 ml of blood (30) and/or PCR from a 1% blood 31 sample in fused-silica capillaries. Although 40 ml is not commonly considered a very small volume, this plastic PCR micro reactor was designed and fabricated with the intent of total on-chip integration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that M13/pUC is a well established cloning vector and the assay was carried out in a buffer environment, the prospective inhibition from a matrix of 'real' sample (blood sample and/or with whole target cells) was not present. The PC plastic serpentine channel PCR micro reactor discussed in this study held a maximum volume of 40 ml and demonstrated a high sensitivity of amplifying 10 E. coli cells (50 fg DNA) from 2% blood sample, as compared to on-chip (glass-silicon) amplification of ng amounts of WBC DNA obtained by filtration from a sample containing 3 ml of blood (30) and/or PCR from a 1% blood 31 sample in fused-silica capillaries. Although 40 ml is not commonly considered a very small volume, this plastic PCR micro reactor was designed and fabricated with the intent of total on-chip integration.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 A high sensitivity amplification from a blood sample in a plastic micro PCR reactor or chip had not been demonstrated to date. An automated and integrated system for high-throughput DNA genotyping directly from blood was reported by Zhang et al 31 Using a hot air thermocycler, samples containing whole blood were directly amplified in a fused-silica capillary and only one concentration (1%) of blood sample PCR was demonstrated, providing ng amounts of DNA as the starting genomic material. In another microchip module for blood sample preparation and amplification, Wilding's group demonstrated direct capture of WBC cells in a glass-silicon microchip with a series of micro filters, from 3 ml of whole human blood, and subsequent amplification of human coagulation factor V from WBC DNAs in the same microchip, 30 in which > 10 ng WBC genomic DNA was used as initial template.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under optimized conditions, separations more than two orders of magnitude faster than traditional slab gel electrophoresis can be performed [3]. CE in linear sieving matrices can be easily automated and parallel capillary systems which combine the speed of analysis with a high overall throughput are currently being used for genetic analysis [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Although CE separations are faster than those of slab gel electrophoresis, a limitation has been that only one sample is processed at a time. CE in an array of up to 96 parallel capillaries represents another way to increase the analysis throughput [4,21,23,25,32,33]. Further miniaturization of the CE system and its integration with sample preparation procedures has been realized on micromachined chips [2,3,6,8,9].…”
Section: Introductionmentioning
confidence: 99%